Hydrated concentrated surfactant composition

The use of sodium benzoate and nonionic phase-modifiers in surfactant compositions enables quick dilution to a homogeneous product with desired viscosity, addressing consumer inconvenience and salt-related challenges.

JP2024545952APending Publication Date: 2024-12-16UNILEVER IP HLDG BV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024531479
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-11-29
Filing Date
2022-11-25
Publication Date
2024-12-16

AI Technical Summary

Technical Problem

Consumers find it inconvenient and time-consuming to dilute concentrated surfactant compositions, resulting in non-homogeneous products with undesirable viscosity, and there is a need for reduced salt levels to prevent corrosion and maintain desirable viscosity.

Method used

A hydratable concentrated surfactant composition using sodium benzoate and nonionic phase-modifying materials to shift the hexagonal phase to a layered crystalline phase, allowing rapid dilution to an isotropic phase with desired viscosity, achieved by specific ratios of anionic surfactants, co-surfactants, and electrolytes.

Benefits of technology

The composition rapidly dilutes to a homogeneous product with viscosity similar to standard personal care products, reducing plastic waste and avoiding salt-related corrosion issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024545952000001
    Figure 2024545952000001
  • Figure 2024545952000002
    Figure 2024545952000002
  • Figure 2024545952000003
    Figure 2024545952000003
Patent Text Reader

Abstract

a) 30 to 50% by weight, based on the total weight of the composition, of an anionic surfactant selected from sodium laureth ether sulfate, sodium parethysulfate, and mixtures thereof; b) 4 to 12 weight percent of a co-surfactant selected from betaine, cocamide monoethanolamide, and mixtures thereof, based on the total weight of the hydratable concentrated surfactant composition; c) 0.2 to 3 weight percent of sodium benzoate, based on the weight of the total composition; d) an additional phase modifier selected from nonionic esters containing carbon chains having a carbon chain length of C8 to C12; e) 0.2 to 3 weight percent of a viscosity modifier, based on the weight of the total composition, which is an inorganic electrolyte; f) 10 to 60 weight percent of water, based on the weight of the total composition; the surfactant is in a lamellar phase; the hydratable concentrated surfactant composition has a pH of 3 to 6; and the hydratable concentrated surfactant composition has a viscosity of 8,000 to 200,000 mPas- when measured at 30° C. on a Brookfield DV2T using a Spindle RV-05 at 20 rpm for 60 seconds on a Helipath stand. 1 (cps); the weight ratio of a) said anionic surfactant to b) said co-surfactant is from 3:1 to 10:1; and the weight ratio of sodium benzoate (c) to total surfactant (a)+(b) is from 1:5 to 1:75, preferably from 1:10 to 1:65, and most preferably from 1:15 to 1:50.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hydratable concentrated surfactant cleansing composition having low salt levels and a method for making the end-use composition by dilution with water. The present invention has particular application in the field of personal care, particularly hair care. [Background technology]

[0002] Liquid-based cleansing compositions, such as shampoos and body washes, are common and enjoyed by many consumers. Such compositions typically contain water as a major component and are often sold in plastic bottles or tubes. The compositions are conventionally formulated to have a viscosity that is customary for consumer use and easy to dispense from the packaging in which they are sold.

[0003] It is often touted that the world's oceans will soon contain more plastic than fish. Given environmental concerns and the desire of consumers and conscious businesses to do more for the planet, there is a strong desire to reduce the use of plastic when selling products, including consumer products.

[0004] Surfactant-containing cleansing products in the form of concentrates are known in the art.

[0005] WO19 / 205086 (Beiersdorf) describes a hair cleansing composition comprising anionic and amphoteric surfactants, natural oils, ethoxylated hydrogenated castor oil and a thickener.

[0006] US 2009 / 0208434 A (Symrise) discloses 3-(4-hydroxy-3-methoxyphenyl)-1-(4-hydroxyphenyl)-1-propanone and its use in cosmetics and pharmaceuticals, such as concentrated body washes and shampoos.

[0007] WO 1994 / 16680 (Unilever) discloses an aqueous dilution-thickened concentrated personal cleaning composition comprising a) 20-60% by weight of a surfactant other than a soap or a primary alcohol sulfate in a lamellar phase, and b) 1-20% by weight of an electrolyte.

[0008] WO10149425 (Unilever) discloses a concentrated shampoo composition comprising 27-70% by weight of a cleansing surfactant, a conditioning gel phase, a gel phase comprising a short chain diol and an oil; a fatty material, a gel network anionic surfactant and a cationic surfactant, said conditioning gel network having no overall charge or being anionic.

[0009] WO2020 / 044235 (Lonza) discloses a highly concentrated, flowable liquid anionic surfactant composition comprising (a) an anionic surfactant solution comprising an alkyl ether sulfate, (b) a viscosity modifier comprising an aromatic alcohol, a linear or branched polyglyceryl ester, an alkyl glyceryl ether, or a combination thereof, and (c) an aqueous solvent, wherein the composition maintains flowability when diluted with the aqueous solvent.

[0010] The concentrate is diluted at the time of use to form a liquid product which can then be used in a conventional manner. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] WO19 / 205086 [Patent Document 2] US2009 / 0208434A [Patent Document 3] WO1994 / 16680 [Patent Document 4] WO10149425 [Patent Document 4] WO2020 / 044235 Summary of the Invention [Problem to be solved by the invention]

[0012] A problem encountered with such concentrates is that consumers often dislike having to add additional water to the concentrate and convert it into a usable final product, for example by stirring. Common complaints regarding hydrated products include the time consuming process and the resulting product after adding water is not uniform and has an undesirable consistency.

[0013] In fact, the inventors have found that such concentrated compositions require a long time for the consumer to properly dilute them before use, and that some consumers do not allow sufficient time for complete dilution. It is therefore desirable to provide a concentrate that dilutes quickly so that it can be used more easily and efficiently.

[0014] The properties of the diluted concentrate are also important. Consumers have a strong preference for concentrates because they are associated with quality, spreadability and ease of pouring. Ideally, diluted products of concentrates would have a viscosity similar to that of standard format personal care products such as shampoos.

[0015] Notwithstanding the prior art, there remains a need for improved concentrated shampoo compositions.

[0016] Typically, the phase structure of a typical non-concentrated shampoo composition is an isotropic phase. However, when the surfactant concentration is increased to provide a concentrated shampoo, the typical rheology shifts from the isotropic phase to a hexagonal phase. The hexagonal phase provides a composition that is too viscous for a typical consumer and can only be diluted very slowly.

[0017] Inorganic salts, such as sodium chloride, potassium chloride, and the like, are commonly used in surfactant-containing formulations to help control viscosity. In manufacturing, an additional problem arises in that the salts can cause corrosion problems in manufacturing vessels. There is a need to reduce salt levels without reducing the final viscosity of the diluted final product.

[0018] We have now discovered that the addition of a phase modifier allows for the reduction of salt without compromising the desirable high quality viscosity properties of the formulation.

[0019] The inventors have now surprisingly found that by using sodium benzoate and additional non-ionic phase modifying materials, highly concentrated compositions that are hexagonal phase can be modified to a lamellar crystalline phase, which upon dilution can rapidly change to an isotropic phase to form a final product having a desirable viscosity.

[0020] The composition can be applied as a small amount of concentrate and diluted at the point of use, so it is ready to use when needed. Refillable packaging allows dilution with water, ensuring less plastic waste. [Means for solving the problem]

[0021] Definition of the invention In a first aspect, the present invention provides a hydratable concentrated surfactant composition comprising: a) 30 to 50% by weight, based on the total weight of the composition, of an anionic surfactant selected from sodium laureth ether sulfate, sodium parethysulfate, and mixtures thereof; b) 4 to 12 weight percent of a co-surfactant selected from betaine, cocamide monoethanolamide, and mixtures thereof, based on the total weight of the hydratable concentrated surfactant composition; c) 0.2 to 3% by weight of sodium benzoate, based on the weight of the total composition; d) an additional phase modifier selected from non-ionic esters containing a carbon chain having a carbon chain length of C8 to C12, preferably C8 to C10; e) 0.2 to 3 weight percent of a viscosity modifier which is an inorganic electrolyte, based on the weight of the total composition; f) 10 to 60% by weight of water based on the weight of the total composition Including, the surfactant is in a lamellar phase; The hydratable concentrated surfactant composition has a pH of 3 to 6; The hydratable concentrated surfactant composition has a viscosity of 8,000 to 200,000 mPas- when measured at 30° C. with a Brookfield DV2T using a Spindle RV-05 at 20 rpm for 60 seconds on a Helipath stand. 1 (cps); the weight ratio of a) the anionic surfactant to b) the co-surfactant is from 3:1 to 10:1; A hydratable concentrated surfactant composition is provided having a weight ratio of sodium benzoate (c) to total surfactants (a)+(b) of from 1:5 to 1:75, preferably from 1:10 to 1:65, and most preferably from 1:15 to 1:50.

[0022] The end use composition may be prepared by hydrating the hydratable concentrated surfactant composition of the first aspect by dilution with water.

[0023] Preferably, the end use composition has a weight ratio of hydratable concentrated surfactant composition to water of from 1:1 to 1:6, more preferably from 1:1 to 1:5.

[0024] Preferably, the end use composition has a viscosity of 1000 to 10,000 mPas when measured on a Brookfield DV2T at 30° C. using a Spindle RV-05 on a Helipath stand at 20 rpm for 60 seconds. -1 (cps), preferably 1000 to 8,000, more preferably 1000 to 7,500 mPas -1 (cps) viscosity.

[0025] The hydratable concentrated surfactant composition has a surface active agent viscosity of 8,000 to 200,000 mPas -1(cps), preferably 10,000 to 100,000, more preferably 15,000 to 90,000 mPas -1 (cps), most preferably 15,000 to 75,000 mPas -1 (cps) viscosity.

[0026] Dilution reduces the viscosity, resulting in a viscosity of 1000-10,000 mPas when measured on a Brookfield DV2T at 30°C using a Spindle RV-05 at 20 rpm for 60 seconds on a Helipath stand. -1 (cps), preferably 1000 to 8,000 mPas -1 (cps), more preferably 1000 to 7,500 mPas -1 The resulting end use composition has a viscosity of (cps).

[0027] In a second aspect, the present invention provides a method for making an end use composition comprising diluting the hydratable concentrated surfactant composition of the first aspect with water. Preferably, the method comprises subjecting a mixture of the hydratable composition and water to moderate shear, such as shaking or stirring, to obtain the end use composition in less than 10 minutes, preferably less than 5 minutes, more preferably less than 3 minutes, even more preferably less than 2 minutes, even more preferably less than 1 minute, and most preferably less than 30 seconds.

[0028] Preferably, the hydratable concentrated surfactant composition is diluted at a weight ratio of hydratable concentrated surfactant composition to water of 1:1 to 1:6, more preferably 1:1 to 1:5. Preferably, the temperature of the water is 10 to 50°C.

[0029] A diluted product is formed prior to its use. Preferably, the composition is diluted in a suitable container prior to its application, for example to the hair or skin. In a preferred embodiment, the container is a refillable package. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] In preparing the hydratable concentrated surfactant composition, the desired ingredients can be mixed using conventional equipment under moderate shear and atmospheric conditions at a temperature of from 35 to 80°C.

[0031] Water is added to the hydratable concentrated surfactant composition to produce the end-use composition. Moderate shear, such as shaking (or stirring) in a container, produces the end-use composition in less than 5 minutes, preferably less than 3 minutes, and most preferably less than 2 minutes. In one embodiment of the present invention, the end-use composition is produced in less than 1 minute, and more preferably less than 30 seconds. The end-use composition is then ready for immediate use.

[0032] In the present invention, the hydratable concentrated surfactant composition should be formulated such that upon dilution, the desired component / component level (such as sulfate level) in the end-use composition is achieved.

[0033] A hydratable concentrated surfactant composition will have a starting viscosity that is higher than the final viscosity after water is added to make the end-use composition.

[0034] Hydrable concentrated surfactant compositions and end use compositions typically have a pH of 3-6.

[0035] The end use composition is made by combining water and the hydratable concentrated surfactant composition and mixing (with stirring, preferably with moderate shear such as shaking) to produce the end use composition.

[0036] The compositions of the present invention are cosmetic and non-therapeutic.

[0037] The end use composition may be a personal care cleaning composition, preferably a shampoo, a make-up wash, a facial cleanser, a hand wash or a personal care liquid body wash, more preferably a shampoo or a body wash, most preferably a shampoo.

[0038] The end use compositions are suitable for wiping or rinsing, preferably with water.

[0039] In one embodiment of the present invention, the end use shampoo composition may preferably have a viscosity of 1,000 to 6,000.

[0040] Viscosity is measured on a Brookfield DV2T using a Spindle RV-05 at 30° C. on a Helipath stand at 20 rpm for 60 seconds unless otherwise stated.

[0041] Preferably, the hydratable concentrated surfactant composition of the present invention is free of silicone. In the context of the present invention, "free from" means having less than 0.4% by weight, more preferably less than 0.1% by weight, even more preferably less than 0.05% by weight, even more preferably less than 0.001% by weight, even more preferably less than 0.0001% by weight, and most preferably 0% by weight of silicone based on the weight of the total composition.

[0042] Anionic Surfactants The hydratable concentrated surfactant composition of the present invention comprises an anionic surfactant selected from sodium laureth ether sulfate (SLES), sodium pareth ether sulfate (SPES), and mixtures thereof.

[0043] In a typical hydratable concentrated surfactant composition of the present invention, the level of anionic surfactant will generally range from 30 to 50%, preferably 40 to 50% (by weight based on total weight of the composition and 100% active).

[0044] Co-surfactant The hydratable concentrated surfactant compositions of the present invention include a co-surfactant selected from betaine, cocamide monoethanolamide (CMEA), and mixtures thereof.

[0045] The level of co-surfactant is from 4 to 12% by weight, preferably from 4 to 10% by weight, and most preferably from 4 to 7.5% by weight, based on the total weight of the hydratable concentrated surfactant composition and on a weight basis based on 100% active level.

[0046] Betaines suitable for use in the present invention can be represented by the general formula: [ka] [In the formula, R 10 is C6-C30, particularly C6-C24 alkyl, z is 0 or 1, R 11 and R 12 is independently alkyl, hydroxyalkyl, or carboxyalkyl of 1 to 3 carbon atoms, and y is 2 or 3; and salts thereof. In one embodiment, the group R 10 At least half of the groups R 10 At least half of R is C10-C14 alkyl. 10 can be saturated or unsaturated. In one embodiment, R 10 is derived from coconut oil or palm kernel oil. 11 and R 12 is methyl.

[0047] The betaines of formula (IV) are simple betaines: [ka] [In the formula, R 10 , R 11 , and R 12 are as described above.], and amidobetaines: [ka] [In the formula, R 10 , R 11 , R 12 , and y are as defined above. Includes.

[0048] Preferred betaines are oleyl betaine, caprylamidopropyl betaine, lauramidopropyl betaine, isostearyl amidopropyl betaine, and cocamidopropyl betaine, and mixtures thereof. Most preferably, the co-surfactant is cocamidopropyl betaine.

[0049] Most preferably, the co-surfactant is selected from cocamidopropyl betaine (CAPB), cocamide monoethanolamide (CMEA) and mixtures thereof.

[0050] The weight ratio of a) anionic surfactant to b) co-surfactant is from 3:1 to 10:1, preferably from 3.5:1 to 9:1, and most preferably from 3.7:1 to 8.7:1.

[0051] Sodium benzoate and additional phase modifiers The hydratable concentrated surfactant compositions of the present invention include sodium benzoate, which the inventors have discovered shifts the hexagonal phase to a lamellar phase, facilitating rapid dilution.

[0052] Sodium benzoate is present in an amount of from 0.2% to 3% by weight, preferably from 0.5% to 3% by weight, based on the weight of the total composition.

[0053] The weight ratio of sodium benzoate to the total surfactants (a)+(b) is from 1:5 to 1:75, preferably from 1:10 to 1:65, more preferably from 1:15 to 1:50, and most preferably from 1:15 to 1:35.

[0054] The composition of the present invention comprises an additional phase modifier selected from non-ionic esters containing carbon chains having a carbon chain length of from C8 to C12, preferably from C8 to C10.

[0055] Preferred non-ionic phase modifiers are long chain esters having carbon chain lengths of C8 to C12, preferably C8 to C10.

[0056] Preferred long chain esters as non-ionic phase conditioners are selected from alkyl acetates, fatty alcohols and fatty acids, most preferably alkyl acetates.

[0057] Preferred alkyl acetate nonionic phase modifiers are selected from octyl acetate, decyl acetate, dodecyl acetate and mixtures thereof, most preferably decyl acetate.

[0058] The additional phase modifier is present in an amount of from 0.2% to 3% by weight, preferably from 0.5% to 3% by weight, based on the weight of the total composition.

[0059] Viscosity modifier The hydratable concentrated surfactant composition of the present invention contains a viscosity modifier, which is an inorganic electrolyte, to increase the viscosity of the diluted final composition.The inorganic electrolytes suitable for use in the present invention include metal chlorides (e.g., sodium chloride, potassium chloride, calcium chloride, magnesium chloride, zinc chloride, ferric chloride, aluminum chloride, etc.) and metal sulfates (e.g., sodium sulfate, magnesium sulfate, etc.) and mixtures thereof.The inorganic electrolyte is used to give viscosity to the diluted final composition.Without it, the final composition would be too thin for consumers to accept.

[0060] Mixtures of any of the above mentioned materials may also be suitable.

[0061] Examples of inorganic electrolytes suitable for use in the present invention include sodium chloride, potassium chloride, magnesium sulfate, and mixtures thereof.

[0062] The level of inorganic electrolyte in the composition of the present invention ranges from 0.2 to 3% by weight, preferably from 0.3 to 2.5% by weight (based on the total weight of the composition).

[0063] water Water accounts for 10 to 60% by weight, preferably 20 to 60% by weight, based on the total weight of the composition.

[0064] The pH of the hydratable composition and end-use composition is 3-6, preferably 3.5-5.5, more preferably 3.5-5, and most preferably 3.8-4.8. Suitable pH modifiers may be used to modify or buffer the pH. Such pH modifiers include triethylamine, NaOH, KOH, H2SO4, HCl, citric acid, or mixtures thereof. The pH modifier is added in an amount to provide the desired final pH. The pH value can be assessed using commercially available equipment, such as a pH meter available from Thermo Scientific®.

[0065] Other ingredients Compositions according to the present invention may include any of a number of ingredients common to hair conditioning compositions.

[0066] Other ingredients may include preservatives, conditioning enhancing polymers, colorants, polyhydric alcohols such as glycerin and polypropylene glycol, chelating agents, antioxidants such as vitamin E acetate, fragrances, antimicrobial agents, and sunscreens. Each of these ingredients is present in an amount effective to achieve its purpose. Generally, these optional ingredients are included individually at a level of up to about 5% by weight of the total composition.

[0067] Preferably, the additional ingredients include fragrances, preservatives, and conditioning enhancing polymers.

[0068] Preservatives Preservatives are used in the hydratable concentrated surfactant compositions and end-use compositions to prevent the growth of potentially harmful microorganisms.

[0069] Preferably, the preservative comprises an alkali metal salt of benzoic acid, preferably sodium benzoate, and a sequestering agent, preferably ethylenediaminetetraacetic acid (EDTA).

[0070] Preferably, the concentrated compositions of the present invention contain EDTA.

[0071] Any cationic polymer Cationic polymers are preferred ingredients in the compositions of the present invention to enhance conditioning performance.

[0072] Suitable cationic polymers may be cationically substituted homopolymers or may be formed from two or more types of monomers. The weight average (M w ) molecular weight is generally 100,000 to 3,000,000 Daltons. The polymer will have cationic nitrogen-containing groups such as quaternary ammonium groups or protonated amino groups, or mixtures thereof. If the molecular weight of the polymer is too low, the conditioning effect will be insufficient. If it is too high, the extensional viscosity will be high, which may cause problems such as stringing when pouring the composition.

[0073] The cationic nitrogen-containing groups are generally present as substituents on a portion of the total monomer units of the cationic polymer. Thus, if the polymer is not a homopolymer, it may contain spacer non-cationic monomer units. Such polymers are described in the CTFA Cosmetic Ingredient Directory, Third Edition. The ratio of cationic to non-cationic monomer units is selected to provide a polymer having a cationic charge density in the required range, which is generally 0.2-3.0 meq / gm. The cationic charge density of the polymer is suitably measured by the Kjeldahl method described in the United States Pharmacopeia under Chemical Test for Nitrogen Determination.

[0074] Suitable cationic polymers include, for example, copolymers of vinyl monomers having cationic amine or quaternary ammonium functional groups with water-soluble spacer monomers such as (meth)acrylamides, alkyl and dialkyl (meth)acrylamides, alkyl (meth)acrylates, vinyl caprolactone and vinyl pyrrolidine. The alkyl- and dialkyl-substituted monomers preferably have C1-C7 alkyl groups, more preferably C1-3 alkyl groups. Other suitable spacers include vinyl esters, vinyl alcohol, maleic anhydride, propylene glycol and ethylene glycol.

[0075] The cationic amines can be primary, secondary, or tertiary amines, depending on the particular species and the pH of the composition. Generally, secondary and tertiary amines, especially tertiary amines, are preferred.

[0076] Amine substituted vinyl monomers and amines can be polymerized in the amine form and then converted to ammonium by quaternization.

[0077] The cationic polymer may comprise a mixture of monomer units derived from amine and / or quaternary ammonium substituted monomers and / or compatible spacer monomers.

[0078] Suitable (non-limiting) cationic polymers include: - cationic diallyl quaternary ammonium-containing polymers, including, for example, dimethyldiallylammonium chloride homopolymer and copolymer of acrylamide and dimethyldiallylammonium chloride, referred to in the industry (CTFA) as Polyquaternium 6 and Polyquaternium 7, respectively; - mineral acid salts of aminoalkyl esters of homo- and copolymers of unsaturated carboxylic acids having 3 to 5 carbon atoms (described in U.S. Pat. No. 4,009,256); - cationic polyacrylamides (described in WO 95 / 22311).

[0079] Other cationic polymers that can be used include cationic polysaccharide polymers such as cationic cellulose derivatives, cationic starch derivatives, and cationic guar gum derivatives.

[0080] Cationic polysaccharide polymers suitable for use in the compositions for use in the present invention include monomers of the formula: [ka] where A is an anhydroglucose residue, such as the anhydroglucose residue of starch or cellulose, and R is an alkylene, oxyalkylene, polyoxyalkylene, or hydroxyalkylene group, or a combination thereof. 1 , R 2 and R 3 independently represent an alkyl, aryl, alkylaryl, arylalkyl, alkoxyalkyl, or alkoxyaryl group, each group containing up to about 18 carbon atoms. The total number of carbon atoms in each cationic moiety (i.e., R 1 , R 2 and R 3 (the sum of carbon atoms in) is preferably about 20 or less, and X is an anionic counterion.

[0081] Another type of cationic cellulose includes the polymeric quaternary ammonium salt of hydroxyethyl cellulose reacted with lauryldimethylammonium substituted epoxide referred to in the industry (CTFA) as Polyquaternium 24. These materials are available, for example, from Amerchol Corporation under the trade name Polymer LM-200.

[0082] Other suitable cationic polysaccharide polymers include quaternary nitrogen-containing cellulose ethers (e.g., as described in U.S. Pat. No. 3,962,418) and copolymers of etherified cellulose and starch (e.g., as described in U.S. Pat. No. 3,958,581). Examples of such materials include the Polymer LR and JR series from Dow, commonly referred to in the industry (CTFA) as Polyquaternium 10.

[0083] A particularly suitable type of cationic polysaccharide polymer that can be used is a cationic guar gum derivative, such as guar hydroxypropyltrimethylammonium chloride (commercially available from Rhodia under the JAGUAR trademark series). Examples of such materials are JAGUAR C13S, JAGUAR C14, JAGUAR C17.

[0084] Mixtures of any of the above cationic polymers may also be used.

[0085] The cationic polymer will generally be present in shampoo compositions for use in the present invention at a level of from 0.01 to 5%, preferably from 0.02 to 1%, more preferably from 0.05 to 0.8%, based on the total weight of the cationic polymer based on the total weight of the composition.

[0086] The examples provided are intended to facilitate understanding of the invention and are not intended to limit the scope of the claims.

[0087] Unless otherwise stated, all amounts are in weight percent, based on the total weight of the composition. EXAMPLES

[0088] Example 1: Compositions 1 to 5 according to the present invention and comparative compositions A to F Concentrated shampoo compositions 1 to 5 were prepared in accordance with the present invention. Comparative concentrated shampoo compositions A to F were also prepared.

[0089] A standard non-concentrated shampoo was used as the control "0".

[0090] Compositions according to the present invention and comparative compositions are shown in Tables 1 to 3 below.

[0091] Table 1: Compositions of compositions 1 and 2 according to the invention, comparative compositions A and B, and control 0 Ratio of a) anionic surfactant to b) co-surfactant = 6.67:1 Ratio of sodium benzoate (c) to total surfactants (a)+(b) = 1:18.4.

[0092] [Table 1]

[0093] All compositions had a pH range of 3.5 to 5.0.

[0094] Table 2: Compositions 3 and 4 according to the invention and comparative compositions C and D Ratio of a) anionic surfactant to b) co-surfactant = 7.5:1 Ratio of sodium benzoate (c) to total surfactants (a)+(b) = 1:18.4.

[0095] [Table 2]

[0096] All compositions had a pH range of 3.5 to 5.0.

[0097] Table 3: Composition of composition 5 according to the invention and comparative compositions E and F Ratio of a) anionic surfactant to b) co-surfactant = 4.03:1 Ratio of sodium benzoate (c) to total surfactants (a)+(b) = 1:16.1.

[0098] [Table 3]

[0099] All compositions had a pH range of 3.5 to 5.0.

[0100] Concentrated shampoos according to the invention and comparative compositions were prepared by the following method. · Sodium benzoate was dissolved in hot water. · Sodium Laureth Sulfate was added and mixed under constant shear. Add cocamidopropyl betaine and mix until uniform. Next, decyl acetate was added, if present. Finally, citric acid was added to adjust the pH.

[0101] The surfactant phase was determined using the following method.

[0102] The composition was imaged using a polarized light microscope (Zeiss Axio M1m light microscope). A small amount of the composition was placed on a microscope slide and a cover slip was placed on top. The image was captured under cross-polarized light using a 20x objective in transmission mode.

[0103] Example 2: Dilution of compositions according to the invention and comparative compositions to obtain end-use diluted products The concentrated compositions were diluted for use as diluted shampoos as follows.

[0104] In the following methods, the amount of concentrate to water used to make 500 g of end use product was 1 part concentrate to 3 parts water. 1. Weigh out the desired amount of concentrate into a clear container. 2. Boil the water and then cool it until the temperature reaches 50°C. 3. Add the correct amount of cooled boiled water to the container. 4. Seal the container and shake for 30 seconds. 5. Leave to stand and evaluate the undissolved portion every minute. The evaluation is repeated at 6.5 minutes and, if necessary, the vessel is shaken again for 30 seconds. 7. Measure the dissolution time and summarize it in the table above.

[0105] The viscosity of the compositions in concentrated and diluted form was measured at 30° C. on a Brookfield DV2T using a Spindle RV-05 on a Helipath stand at 20 rpm for 60 seconds.

Claims

1. 1. A hydratable concentrated surfactant composition comprising: a) 30 to 50% by weight, based on the total weight of the composition, of an anionic surfactant selected from sodium laureth ether sulfate, sodium pareth ether sulfate, and mixtures thereof; b) 4 to 12 wt. % of a co-surfactant selected from betaine, cocamide monoethanolamide, and mixtures thereof, based on the total weight of said hydratable concentrated surfactant composition; c) 0.2-3% by weight of the total composition of sodium benzoate; d) an additional phase modifier selected from non-ionic esters containing carbon chains having a carbon chain length of C8 to C12; e) 0.2 to 3 weight percent of a viscosity modifier which is an inorganic electrolyte, based on the weight of the total composition; f) 10 to 60% by weight of water based on the weight of the total composition. Including, the surfactant is in a lamellar phase; the hydratable concentrated surfactant composition has a pH of 3 to 6; the hydratable concentrated surfactant composition has a viscosity of 8,000 to 200,000 mPas-1 (cps) as measured at 30° C. with a Brookfield DV2T using a Spindle RV-05 on a Helipath stand for 60 seconds at 20 rpm; a weight ratio of a) said anionic surfactant to b) said co-surfactant is from 3:1 to 10:1; A hydratable concentrated surfactant composition having a weight ratio of sodium benzoate (c) to total surfactants (a)+(b) of from 1:5 to 1:75, preferably from 1:10 to 1:65, more preferably from 1:15 to 1:50, and most preferably 1:

35.

2. 2. A concentrated composition according to claim 1, wherein the additional phase conditioner is selected from alkyl acetates, fatty alcohols and fatty acids, preferably alkyl acetates.

3. 3. A concentrated composition according to claim 1 or claim 2, wherein the additional phase modifier is selected from octyl acetate, decyl acetate, dodecyl acetate and mixtures thereof, preferably decyl acetate.

4. 10. A concentrated composition according to any preceding claim, wherein the co-surfactant is selected from cocamidopropyl betaine, cocamide monoethanolamide and mixtures thereof.

5. 10. A concentrated composition according to any preceding claim, wherein the inorganic electrolyte is selected from metal chlorides, metal sulfates and mixtures thereof.

6. 10. A concentrated composition according to any preceding claim, wherein the weight ratio of a) said anionic surfactant to b) said co-surfactant is from 3.5:1 to 9:

1.

7. 10. The concentrated composition of any preceding claim, further comprising ethylenediaminetetraacetic acid.

8. 10. The composition of any preceding claim, which is silicone-free.

9. A method comprising the step of diluting the wettable composition of any one of claims 1 to 8 with water.

10. 10. The method of claim 9, comprising subjecting a mixture of the hydratable composition and water to shear, such as shaking or stirring, to produce said end-use composition in less than 10 minutes.

11. The method of claim 9 or claim 10, wherein the weight ratio of the hydratable concentrated surfactant composition to water is from 1:1 to 1:

6.

12. The method of any one of claims 9 to 11, wherein the end use composition is in an isotropic phase.

13. The end use composition has a viscosity of 2000 to 10,000 mPas when measured at 30° C. with a Brookfield DV2T using a Spindle RV-05 on a Helipath stand at 20 rpm for 60 seconds. -1The method of any one of claims 9 to 12, wherein the composition has a viscosity of (cps).

Citation Information

Patent Citations

  • Concentrated surfactant composition with controlled viscosity

    JP1995507833A

  • Concentrated liquid detergent composition

    JP1998001694A

  • Liquid cleansing composition comprising lamellar phase with low salt level

    JP2003509573A

  • Concentrated liquid detergent composition and method for production thereof

    JP2011219663A

  • Personal Care Compositions

    US20180369102A1